Behaviour change interventions addressing patient antibiotic treatment-seeking behaviour for respiratory tract infections in primary and community care settings: a scoping review - Andrew Murphy; Greg Sheaf; Cristin Ryan; Gerard J Molloy; Anthony Maher; Kevin Roche; Eimear Morrissey (BMJ Open)
Objectives This scoping review aimed to map studies on behaviour change interventions that address antibiotic treatment-seeking behaviour for respiratory tract infections in primary and community care settings.Design This review is based on the Joanna Briggs Institute guidelines for scoping reviews, guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews.Data sources A literature search in January 2024 and May 2024 was performed across Medline, Embase, CINAHL, PsycINFO, Web of Science Core Collection, Scopus, EThOS and Google Scholar was performed.Eligibility criteria Eligible studies described behaviour change interventions in primary and community care settings, published from 2000 onward across all countries.Data extraction and synthesis Descriptive data relating to study details and intervention functions were gathered and organised according to the Capability, Opportunity, Motivation and Behaviour change framework in a predeveloped data extraction sheet. Dual data extraction occurred, and inter-rater reliability results are reported (K=0.83).Results The scoping review identified 38 eligible studies, which consisted of randomised controlled trials (7/38), cluster randomised controlled trials (6/38), randomised experiments (5/38), cross-sectional studies (5/38), qualitative investigations (5/38) and quasi-experimental designs (4/38). Most interventions focused on educational resources (15/38), digital tools (7/38) and community campaigns (6/38), with fewer targeting decision-making processes (4/38) or psychological drivers of antibiotic-seeking behaviour (3/38). Only one study was conducted in low-income and middle-income countries, and only one separately assessed behaviour change as a measured outcome.Conclusions This scoping review highlights a wide range of research methodologies within the topic area. There was some limited evidence of intervention efficacy for antibiotic prescription rates, particularly interventions focused on enhancing knowledge and access to resources. However, more emphasis is needed on standardising outcome measures and evaluating long-term outcomes.